Contrail-free aero-engines. - Qureshi, Sarah (Cranfield University, 2016)
This thesis presents a contrail-free aero-engine designed to reduce the aviation induced global warming through the development of a condensation and containment mechanism for the exhaust water vapour content of an aero-engine. This mechanism intends to eliminate the source of contrail formation. A pressure-based turbomachinery defined as the water expeller is developed and introduced as a modular attachment to a standard aero-engine. It employs the use of centrifugal compression to generate pressure in the exhaust gas leading to a phase change that precipitates out the water content of the core exhaust gases. The water produced is drained out of the device and collected within the engine. The heat dissipated by water during condensation is absorbed by the remaining combustion gases. The design of the centrifugal water expeller is derived from a patented invention and evolved into a practical system. The theory of centrifugal extraction is explained and the underlying physics is established. This proceeds with a thermodynamic analysis whereby data for mechanical design is computed and advanced towards a prototype ready engineering model inclusive of structural design and structural analysis. The power requirements of this system are determined using thermodynamic data. In the preliminary design, the inclusion of the water expelling device results in a thirty percent increase in the length of the engine which has a likelihood of being reduced through optimization. The initial design parameters of the system are obtained from the performance analysis of a standard high-bypass three-spool turbofan engine and the study of atmospheric science and water physics. The design of the condensation device is validated through the study of the thermo-chemistry of the exhaust gases and a simple heat transfer analysis. The inter-gaseous exchange of energy at the molecular level during the process of condensation is also quantified. The performance of the standard engine with the integration of the centrifugal water expeller is analysed and progressed towards the performance evaluation of a standard wide body large aircraft with four contrail-free engines on board. Initial estimates indicate an increase in the weight of the engine by twenty five percent with the installation of the centrifugal water expeller onto the engines. This is merely a two percent increase in the overall weight of the aircraft. The integration of the mechanical device with the aero-engine results in an environmentally favourable engine-aircraft configuration with a three percent thrust penalty which is recognized as the acceptable trade-off for environmental benefits.
Keywords: contrail-free; aero-engine; centrifugal extraction; thermo-chemistry; inter-gaseous exchange; water expeller